1995
DOI: 10.1136/bmj.310.6993.1491
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of an association between non-Hodgkin's lymphoma and skin cancer

Abstract: Objective-To investigate a possible link between exposure to ultraviolet light and the almost epidemic increase in non-Hodgkin's lymphoma worldwide. Because ultraviolet light is known to cause skin cancers, the association between non-Hodgkin's lymphoma and skin cancer was studied.Design-Secondary occurrence of either malignant melanoma or squamous cell skin cancer in cohorts of patients with a first diagnosis of either non-Hodgkin's lymphoma or chronic lymphocytic leukaemia, and vice versa, were studied. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
246
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(261 citation statements)
references
References 23 publications
12
246
3
Order By: Relevance
“…On present evidence, none of these is true. People who have had cutaneous SCC 8,9 and BCC 9 consistently have a higher than expected frequency of subsequent NHL in cancer registry cohort studies, and we found that a past history of treatment for skin cancer (unverified) in this population was associated with a slight, nonsignificant increase in risk of NHL, 10 a finding consistent with the only other study of self-reported past skin cancer in people with NHL. 41 We have also previously reported from this study that fair skin and poor tanning ability are associated with a small increase in risk of NHL.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On present evidence, none of these is true. People who have had cutaneous SCC 8,9 and BCC 9 consistently have a higher than expected frequency of subsequent NHL in cancer registry cohort studies, and we found that a past history of treatment for skin cancer (unverified) in this population was associated with a slight, nonsignificant increase in risk of NHL, 10 a finding consistent with the only other study of self-reported past skin cancer in people with NHL. 41 We have also previously reported from this study that fair skin and poor tanning ability are associated with a small increase in risk of NHL.…”
Section: Resultssupporting
confidence: 87%
“…2 There is, though, an inconsistency in these patterns: NHL incidence and mortality have been reported to rise with increasing latitude and fall with increasing estimated ambient ultraviolet irradiance in the United States. 4 -7 Positive associations between a personal history of squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), which may indicate high sun exposure, and risk of NHL in cancer registry cohorts 8,9 and weak evidence that sun sensitivity is associated with an increased risk of NHL in individuals, 10 however, offer additional support for a causal association.…”
mentioning
confidence: 99%
“…It has been hypothesised that a person's risk of NHL may be influenced by ultraviolet (UV) light (Cartwright et al, 1994;Adami et al, 1995). The recent steep increase in NHL incidence observed in persons of both sexes, and predominantly in the young and middle-aged, is in accordance with such a hypothesis.…”
Section: Discussionmentioning
confidence: 91%
“…For skin SCC, the total life-time UVR-dose is considered important; for melanoma high intermittent exposures in childhood and adolescence are considered important (Adami et al, 1995;English et al, 1997). A second aetiological factor is defective immune function and skin SCC and NHL are greatly increased in organ transplant patients (Kinlen, 1992;IARC, 1997).…”
Section: Melanoma and Scc Of Skin Following Hlpdmentioning
confidence: 99%